Spray‐dried plasma and fresh frozen plasma modulate permeability and inflammation in vitro in vascular endothelial cells. (10th January 2013) - Wataha, K.; Menge, T.; Deng, X.; Shah, A.; Bode, A.; Holcomb, J.B.; Potter, D.; Kozar, R.; Spinella, P.C.; Pati, S.
Abstract : Background: After major traumatic injury, patients often require multiple transfusions of fresh frozen plasma (FFP) to correct coagulopathy and to reduce bleeding. A spray‐dried plasma (SDP) product has several logistical benefits over FFP use in trauma patients with coagulopathy. These benefits include ease of transport, stability at room temperature, and rapid reconstitution for infusion. Our past work suggests that FFP promotes endothelial stability by inhibiting endothelial permeability. Study Design and Methods: The main goal of this project is to determine if solvent‐detergent‐treated SDP is equivalent to FFP in inhibiting vascular endothelial cell (EC) permeability and inflammation in vitro. Furthermore, this study aimed to determine if solvent‐detergent treatment and spray drying of plasma alters the protective effects of FFP on EC function. The five groups tested in our studies are the following: 1) fresh frozen‐thawed plasma (FFP); 2) solvent‐detergent‐treated FFP; 3) solvent‐detergent‐treated SDP; 4) lactated Ringer's solution; and 5) Hextend. Results: This study demonstrates that in vitro SDP and FFP equivalently inhibit vascular EC permeability, EC adherens junction breakdown, and endothelial white blood cell binding, an effect that is independent of changes in Vascular Cell Adhesion Molecule 1, Intracellular Adhesion Molecule 1, or E‐selectin expression on ECs. Solvent‐detergent treatment of FFP does not alter the protective effects of FFP on endothelial cell function in vitro. Conclusion: These data suggest the equivalence of FFP and SDP on modulation of endothelial function and inflammation in vitro.